Characterization of anthracnose resistance caused by glomerella cingulata and productivity of five andean blackberry genotypes (rubus glaucus benth.) (2013)
The research aimed to evaluate promising materials having both resistance to Anthracnose and high productivity. The experiment was established at the Betania village, municipality of Guática, department of Risaralda, located to 2,160 mamsl. Five blackberry genotypes previously selected by the research group on Biodiversity and Biotechnology of the Universidad Tecnológica de Pereira, Colombia. Ten months after establishment of the experiment, the plants were inoculated with two pathogenic isolates of Colletotrichum gloeosporioides at a concentration of 1.2 x 106 conidia ml-1 of water. The response variables were incidence (presence or absence of lesions on the stems), severity (using a scale of 1 to 9) and yield (kg per plant). The five genotypes tested were classified into three groups according to their resistance to the pathogen and its performance: the first, formed by UTP-7 and UTP-8, which produced 21 and 17.6 t ha-1 , respectively; the second, by UTP-1 which produced 14.3 t ha-1, and the third, by UTP-2 and UTP-4 with 9.8 and 7.9 t ha-1, respectively.